1994
DOI: 10.1126/science.7997883
|View full text |Cite
|
Sign up to set email alerts
|

Potentiated Transmission and Prevention of Further LTP by Increased CaMKII activity in Postsynaptic Hippocampal Slice Neurons

Abstract: Calcium-calmodulin-dependent protein kinase II (CaMKII) is a necessary component of the cellular machinery underlying learning and memory. Here, a constitutively active form of this enzyme, CaMKII(1-290), was introduced into neurons of hippocampal slices with a recombinant vaccinia virus to test the hypothesis that increased postsynaptic activity of this enzyme is sufficient to produce long-term synaptic potentiation (LTP), a prominent cellular model of learning and memory. Postsynaptic expression of CaMKII(1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
183
1
2

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 307 publications
(198 citation statements)
references
References 55 publications
12
183
1
2
Order By: Relevance
“…In particular, this kinase is widely believed to be a critical mediator of long term potentiation (LTP), a cellular mechanism that is thought to underlie learning and memory (Bliss and Collingridge, 1993). Several studies have demonstrated that CaMKII is necessary for the induction of LTP (Malinow et al, 1989;Malenka et al, 1989;Silva et al, 1992;Giese et al, 1998), and that introduction of activated CaMKII is sufficient to potentiate synaptic responses in neurons (Pettit et al, 1994;Lledo et al, 1995;McGlade-McCulloh et al, 1993). CaMKII is enriched at the postsynaptic density (PSD) (Kennedy et al, 1983;Suzuki et al, 1994;Petersen et al, 2003), a protein-dense specialization at the post-synaptic membrane that is composed primarily of scaffolding proteins, ion channels, and signal transduction enzymes (Ziff, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, this kinase is widely believed to be a critical mediator of long term potentiation (LTP), a cellular mechanism that is thought to underlie learning and memory (Bliss and Collingridge, 1993). Several studies have demonstrated that CaMKII is necessary for the induction of LTP (Malinow et al, 1989;Malenka et al, 1989;Silva et al, 1992;Giese et al, 1998), and that introduction of activated CaMKII is sufficient to potentiate synaptic responses in neurons (Pettit et al, 1994;Lledo et al, 1995;McGlade-McCulloh et al, 1993). CaMKII is enriched at the postsynaptic density (PSD) (Kennedy et al, 1983;Suzuki et al, 1994;Petersen et al, 2003), a protein-dense specialization at the post-synaptic membrane that is composed primarily of scaffolding proteins, ion channels, and signal transduction enzymes (Ziff, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…CaMKII␣ knockout mice show impaired hippocampal long term potentiation, a cellular model for learning and memory (12). Conversely, introduction of CaMKII␣ into neurons augments postsynaptic responses and occludes further electrically induced long term potentiation (13,14).CaMKII␣ undergoes calcium/calmodulin-dependent autophosphorylation on Thr 286 in its regulatory domain, rendering the kinase partially calcium-independent (1, 2). This reaction has been proposed as a "molecular switch," translating transient calcium elevation into prolonged kinase activity (15, 16), which becomes subject to regulation by protein phosphatases.…”
mentioning
confidence: 99%
“…CaMKII␣ knockout mice show impaired hippocampal long term potentiation, a cellular model for learning and memory (12). Conversely, introduction of CaMKII␣ into neurons augments postsynaptic responses and occludes further electrically induced long term potentiation (13,14).…”
mentioning
confidence: 99%
“…Postsynaptic expression of a constitutively active form of CaMKII in hippocampal slices enhances synaptic transmission and prevents further induction of LTP, suggesting that CaMKII and LTP upregulate synaptic transmission through the same mechanism (Pettit et al, 1994;Lledo et al, 1998). The effect of constitutively active CaMKII on synaptic delivery of GluR1 is abrogated by inhibition of PKA, but activation of PKA signaling independently is not enough to induce delivery of the receptors to the synapse (Esteban et al, 2003a).…”
Section: Role Of Ampars In Ltpmentioning
confidence: 98%